A Promising Future of Ferroptosis in Tumor Therapy - Wang, Hui; Lin, Danfeng; Yu, Qianqian; Li, Zhouqi; Lenahan, Cameron; Dong, Ying; Wei, Qichun; Shao, Anwen (Frontiers in Cell and Developmental Biology, 2021)
Currently, mechanisms and therapeutic approaches have been thoroughly studied in various prevalent malignant tumors, such as breast and lung cancer. However, there is inevitable tumor progression and drug resistance. Uncovering novel treatment strategies to inhibit tumor development is important. Ferroptosis, a form of cell death associated with iron and lipid peroxidation, has drawn extensive attention. In this paper, we reviewed the underlying mechanisms of ferroptosis (i.e. iron, glutathione, and lipid metabolism) and its role in various tumors (i.e., lung cancer, liver carcinoma, breast cancer, and pancreatic cancer). Moreover, we summarized ferroptosis-related anti-tumor drugs and emphasized the potential of combined treatment of anti-tumor drugs and radiotherapy in an effort to provide novel anti-tumor treatments.